Повідомлення про підозру та процесуальні аспекти його оскарження - Терещук, С. С.; Tereshchuk, S. S.; ORCID: http://orcid.org/0000-0002-7263-4155 (Вісник Харківського національного університету внутрішніх справ. - 2017. - № 3 (78). - С. 97–104, 2017)
Розглянуто кримінальне процесуальне законодавство України щодо повідомлення особі про підозру. Встановлено неузгодженості та прогалини з цих питань, наведено окремі пропозиції та рекомендації щодо вдосконалення чинного законодавства з цих питань.

The current criminal procedural law concerning notification to a person about suspicion has been considered; it has been established that there are certain inconsistencies; the ways of solving these inconsistencies have been offered. The current legislation concerning appeals against decisions of the officials during the pre-trial investigation has also been analyzed; it has been established that not all procedural decisions can be appealed during the pre-trial investigation. Thus, the notice of suspicion and the results of the search are not objects to appeal, which creates some inconsistency with the provisions of the Constitution of Ukraine, where the Art. 55 stipulates that everyone is guaranteed with the right to appeal in the court against decisions of state authorities, local self-government agencies, officials. The author has also considered the practice of the European Court of Human Rights and the High Specialized Court for the Examination of Civil and Criminal Matters in regard to the acquisition and termination of the status of a suspect within criminal proceedings. It has been established that the legislator did not provide in the provisions of the Art. 303 of the Criminal Procedural Code of Ukraine for the possibility of appealing a notice of suspicion, although there is judicial practice of investigating judges on the cancellation of a notice of suspicion. On the basis of the conducted study, it has been suggested to make some clarifications to the Art. 303 of the Criminal Procedural Code of Ukraine.

Рассмотрено уголовное процессуальное законодательство Украины относительно уведомления лица о подозрении. Установлены некоторые неопределённости относительно этих вопросов, приведены отдельные предложения и рекомендации относительно усовершенствования действующего законодательства по этим вопросам.
A notice of suspicion and procedural aspects of its appealing
Уведомление о подозрении и процессуальные аспекты его обжалования
Терещук, С. С. Повідомлення про підозру та процесуальні аспекти його оскарження / С. С. Терещук // Вісник Харківського національного університету внутрішніх справ. - 2017. - № 3 (78). - С. 97–104.
Tereshchuk, S.S. (2017), “A notice of suspicion and procedural aspects of its appealing” [Povidomlennia pro pidozru ta protsesualni aspekty yoho oskarzhennia], Visnyk Kharkivskoho Natsionalnoho Universytetu Vnutrishnikh Sprav, No. 3, pp. 97–104.
Keywords: Кримінально-процесуальне право. Criminal and Procedure Law. Уголовное процессуальное право; Наукові публікації. Scientific publications. Научные публикации; Україна. Ukraine. Украина; кримінальне провадження; повідомлення про підозру; підозрюваний; слідчий суддя; прокурор; процесуальний керівник; процесуальне керівництво; Європейський суд з прав людини; Єдиний реєстр досудових розслідувань; кримінальне правопорушення; criminal proceedings; notice of suspicion; suspect; court; investigating judge; prosecutors; procedural chief; European Court of Human Rights; Uniform registry of pre-trial investigations; criminal offense; уголовное производство; уведомление о подозрении; подозреваемый; следственный судья; процессуальный руководитель; процессуальное руководство; Европейский суд по правам человека; Единый реестр досудебных расследований; уголовное правонарушение